The role playing by social media in COVID-19 to exacerbate anxiety and depression among Pakistani community - Khan, Sadia Yasir; Rashid, Farah; Ansari, Sadaf Konain; Khalid, Sadaf; Abdullah, Ahmed; Farhin, Shehla (Journal of Rawalpindi Medical College, 2023)
Introduction: The purpose of the worldwide lockdown was to impede the spread of this virus via social distancing. WHO detected symptoms like anxiety, stress, fear which have affected people’s psychology across the globe due to loneliness, substance abuse, depression and constant fear? With the surge of information regarding COVID-19 on social media (myths and beliefs), it certainly played a major role for communities’ psychology all around the globe. Methods: A cross sectional study design was chosen with convenient sampling size of 800 via online. Questionnaire shared through online social media platforms. Statistical analysis was done through SPSS version 21 and responses were taken as frequencies, percentages and chi-square test. Results: there was a significant association between highly educated peoples and social media usage with p-value less than 0.000 suggestive of myths generating decline of mental health. Conclusion: COVID-19 information available over social media was used by everyone and considered as authentic. Therefore, control measures and legislation should be applied on them to restrict the ambiguity. Key-words: Social media; COVID-19; Myths; life worth; save humanity; Attitude;